2015
DOI: 10.1670/12-265
|View full text |Cite
|
Sign up to set email alerts
|

Hibernation Site Philopatry in Northern Pine Snakes (Pituophis melanoleucus) in New Jersey

Abstract: Northern Pine Snakes (Pituophis melanoleucus) are one of the few snakes that spend the winter in underground hibernacula that they excavate. We report the use of hibernacula by Pine Snakes from 1986 to 2012 in the New Jersey Pine Barrens. We determined whether philopatry to a specific hibernaculum varied as a function of age, sex, and location of the hibernaculum. Three hibernacula were occupied nearly continuously for 27 yr by 1 to 27 snakes each year. With known-age snakes (N = 120), captured mainly as hatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We found that Oo was significantly more likely to be detected in soils from within snake hibernacula compared to matched topsoil samples. Many North American snake species, including northern pine snakes, hibernate communally for several months in underground refugia; these snakes often return to the same hibernacula each winter [28][29][30]37]. High concentrations of infected snakes in a confined space for an extended period of time could result in the build-up of shed Oo in the surrounding soil, thus resulting in an increased likelihood of detection compared to soils sampled above ground where snakes are more mobile and dispersed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that Oo was significantly more likely to be detected in soils from within snake hibernacula compared to matched topsoil samples. Many North American snake species, including northern pine snakes, hibernate communally for several months in underground refugia; these snakes often return to the same hibernacula each winter [28][29][30]37]. High concentrations of infected snakes in a confined space for an extended period of time could result in the build-up of shed Oo in the surrounding soil, thus resulting in an increased likelihood of detection compared to soils sampled above ground where snakes are more mobile and dispersed.…”
Section: Discussionmentioning
confidence: 99%
“…However, repeated and consistent environmental detections and the demonstrable ability to culture the fungus from the environment implicates hibernaculum soils as potential environmental reservoirs through the mechanism of pathogen persistence. Given that snakes congregate and spend prolonged periods of time within hibernacula while infected and demonstrate philopatry to hibernation sites [30], it is easy to see how hibernaculum soils may act as both recipient and donor of viable Oo conidia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Snakes are weighed and measured, and hibernacula are reconstructed the same day (we return all snakes into their den on the same day [ 18 ]). Protocols and methods for excavation and study of Pine Snakes in hibernacula are described fully in Burger and Zappalorti [ 18 , 26 ] and Burger et al [ 25 , 37 ].…”
Section: Methods and Protocolmentioning
confidence: 99%
“…Hatchlings typically emerge in early September, and they must find a hibernation site [37]. In the fall, many hatchlings reach the communal hibernacula by following scent trails [37][38][39]. A snake that hatched in September is designated as age 0 in our database when encountered in the fall of its hatching year.…”
Section: Study Species and Study Sitesmentioning
confidence: 99%